Spectrum of Microorganisms, Antibiotic Resistance Pattern, and Treatment Outcomes Among Patients With Empyema Thoracis: A Descriptive Cross-Sectional Study From the Bahawal Victoria Hospital Bahawalpur, Punjab, Pakistan - Atif, Muhammad; Naseem, Mehwish; Sarwar, Sajjad; Mukhtar, Saba; Malik, Iram; Hassan, Muhammad Rauf ul; Iqbal, Muhammad Nouman; Ahmad, Nafees (Frontiers in Medicine, 2021)
Background: This study involves the analysis of spectrum of microorganisms, antibiotic resistance pattern, and treatment outcomes among empyema thoracis patients. This study also analyzes the factors associated with unsuccessful treatment outcome and duration of hospital stay among the patients. Methods: This was a descriptive, cross-sectional study carried out in the Pulmonology Ward of the Bahawal Victoria hospital, Bahawalpur, Pakistan. All patients with empyema thoracis registered at the study site during the period of one year were included in the study. Multivariate regression analysis was used to analyze the factors associated with duration of hospital stay and unsuccessful treatment outcome among the patients. Results: A total110 patients were included in the study. Most of the patients (n= 73, 66.4%) were treated with piperacillin/ tazobactam alone and in combination with either one or more than one antibiotics as an empiric therapy. Culture was positive in 58 (52.7%) patients and the most commonly identified organisms included, gram-negative Pseudomonas aeruginosa (n = 20; 18.8%) and Klebsiella sp. (n= 11, 10%) followed by same proportion of E. coli. The most commonly identified bacterial isolates showed high level of resistance against antibiotics used as an empiric therapy, while these showed low level of resistance against amoxicillin, clarithromycin, ertapenem, colistin, tigecycline, fosfomycin, rifampicin and vancomycin. In this study, 82 (74.5%) patients successfully completed the treatment, while 12 (11%) showed no clinical improvement, 5 (4.5%) lost to follow up and 11 (10%) died. In multivariate binary logistic regression analysis, none of the patient attributes were significantly associated with unsuccessful treatment outcome, while in multivariate linear regression analysis, the factors which were significantly associated with duration of hospital stay included; duration of symptoms less than two weeks prior to admission (p-value= 0.008, beta= -0.247) and resistance to five antibiotic classes (p-value= 0.02, beta= 0.280). Conclusion: Close to 25% of the patients did not complete the treatment successfully. Most of the common bacterial isolates showed high level of resistance against the broad-spectrum antibiotics used as an empiric therapy. This is alarming. However, better sensitivity of common bacterial isolates against standardized first line treatment for empyema thoracis is promising.